If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -24) = 12 Reorder the terms: (-24 + X) = 12 Remove parenthesis around (-24 + X) -24 + X = 12 Solving -24 + X = 12 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + X = 12 + 24 Combine like terms: -24 + 24 = 0 0 + X = 12 + 24 X = 12 + 24 Combine like terms: 12 + 24 = 36 X = 36 Simplifying X = 36
| k^2-7=12 | | b^2-3b-28= | | 0.04(x)+0.10(18-x)=0.06(18) | | X+0.07= | | 12a+19b+6c+2c-2b-2a= | | 7(-4)=2x-3 | | x+0.07x= | | 0.04(x)+0.1(6)=0.06(x+6) | | b^2=-7 | | 2(8-X)=4(X-3) | | 14p+16q+p-6q-6p= | | 3Q^2-118.5Q+328.5=0 | | Y=49x^2+42x+9 | | 5X-3(X-3)=19 | | 8x^3+40x^2+8x+40= | | 15m+6n-5m+11n= | | 27=c(c-6) | | 3x^2+18x=2x^2-81 | | -3X^2+118.5q-328.5=0 | | 4x^2+6x=3x^2-9 | | 5(x-2)-3=5x-10x-17 | | 2(x-1)-7=15 | | 4c^2=25 | | 5m^2+47m=-18 | | z^2-9z=-14 | | 3x^2-41=-110 | | (5w+5)(5w-5)=0 | | z^4-289=0 | | 20p+17q+p-3q-5p= | | -9(t-7)-(t+8)=1 | | (5s-4)(6s-6)=0 | | X^2=5c |